Focus on the physics of biofilms. (27th March 2015) - Lecuyer, Sigolene; Stocker, Roman; Rusconi, Roberto
Abstract: Bacteria are the smallest and most abundant form of life. They have traditionally been considered as primarily planktonic organisms, swimming or floating in a liquid medium, and this view has shaped many of the approaches to microbial processes, including for example the design of most antibiotics. However, over the last few decades it has become clear that many bacteria often adopt a sessile, surface-associated lifestyle, forming complex multicellular communities called biofilms. Bacterial biofilms are found in a vast range of environments and have major consequences on human health and industrial processes, from biofouling of surfaces to the spread of diseases. Although the study of biofilms has been biologists' territory for a long time, a multitude of phenomena in the formation and development of biofilms hinges on physical processes. We are pleased to present a collection of research papers that discuss some of the latest developments in many of the areas to which physicists can contribute a deeper understanding of biofilms, both experimentally and theoretically. The topics covered range from the influence of physical environmental parameters on cell attachment and subsequent biofilm growth, to the use of local probes and imaging techniques to investigate biofilm structure, to the development of biofilms in complex environments and the modeling of colony morphogenesis. The results presented contribute to addressing some of the major challenges in microbiology today, including the prevention of surface contamination, the optimization of biofilm disruption methods and the effectiveness of antibiotic treatments.